2019
DOI: 10.24843/eja.2019.v27.i03.p12
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas Pada CSR Disclosure

Abstract: This study aims to determine the effect of company size, leverage, and profitability on CSR disclosure. The theory used in this study is stakeholder theory and legitimacy theory. The research sample was 29 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2017 with a purposive sampling method. The analysis technique used is the Analysis of Multiple Linear Regression. The results showed that (1) the size of the company has a positive effect on CSR disclosure which shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 1 publication
3
15
0
19
Order By: Relevance
“…And for the sample is used the annual and/or sustainability reports of consumer goods industry, which are listed in IDX and also registered in PROPER from 2017 until 2018. The sampling technique is used purposive sampling, with some criteria: Scale 1 = Very bad = black Scale 2 = Bad = red Scale 3 = Good = blue Scale 4 = very good = green Scale 5 = Excellent = gold Firm size Independent Firm size is about the organizations' total assets and total sales that can determine whether the organization is small or big (Dewi & Yasa, 2017) Measured using logarithm of total asset (Aulia & Agustina ,2015;Embuningtyas, 2018;Nugraha & Juliarto, 2015;and Wang, Song, Yao, 2013) 3, from 56 of the consumer goods industry and mining companies had a standard deviation of 16.51% (rounded from 16.509%) on environmental disclosure from 2017 until 2018. By using GRI -G4 measurement, the average number is 23% or about 7 until 8 items that are averagely implied by the companies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…And for the sample is used the annual and/or sustainability reports of consumer goods industry, which are listed in IDX and also registered in PROPER from 2017 until 2018. The sampling technique is used purposive sampling, with some criteria: Scale 1 = Very bad = black Scale 2 = Bad = red Scale 3 = Good = blue Scale 4 = very good = green Scale 5 = Excellent = gold Firm size Independent Firm size is about the organizations' total assets and total sales that can determine whether the organization is small or big (Dewi & Yasa, 2017) Measured using logarithm of total asset (Aulia & Agustina ,2015;Embuningtyas, 2018;Nugraha & Juliarto, 2015;and Wang, Song, Yao, 2013) 3, from 56 of the consumer goods industry and mining companies had a standard deviation of 16.51% (rounded from 16.509%) on environmental disclosure from 2017 until 2018. By using GRI -G4 measurement, the average number is 23% or about 7 until 8 items that are averagely implied by the companies.…”
Section: Methodsmentioning
confidence: 99%
“…Researches by Dewi & Yasa (2017), Choiriah, Yanto, & Ilhami's (2018), Ezhilarasi & Kabra (2017), Jannah & Muid (2014), Dibia & Onwuchekwa (2015), Burgwal & Vieira (2014), Wang, Song, & Yao (2013), Wijaya (2012) found that firm size significantly influence environmental disclosure. However, this argue against Fatayaningrum (2011) which found that there is insignificant influence on frim size to environmental disclosure, but she found that there is significant influence of profitability to environmental disclosure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normality test which uses the Kolmogorov-Smirnov One-Sample shows a significance of 0.067 higher than the significance level of 0.05 so it can be understood that the residual data is normally distributed. The result of multicollinearity test reveals a VIF number lower than 10 The contribution of company in informing environmental activities carried out by the company (Fashikhah et al, 2018) (Number of items revealed by the company) (number of GRI environmental disclosure items) (Deswanto & Siregar, 2018) Earning management (DA) Earning management exists when managers distort stakeholders about the company's economic performance or to influence contract decisions that rely on financial statements (Healy & Wahlen, 1998) Discretionary Accrual (DA) by modified jones model (Sun et al, 2010) Managerial Ownership (MO) Executives or directors of companies that have stock ownership (Chang & Zhang, 2015) (Number of shares owned @by managers) x 100% (total shares) (Fashikhah et al, 2018) Firm size (FS) Big or small size of a company seen from total assets, total sales, average total sales, and average total assets (Dewi & Yasa, 2017)…”
Section: Results and Discussiosmentioning
confidence: 99%
“…Research by Diantimala & Amril (2018) said that the environmental disclosure of companies participating in PROPER in Indonesia only held an average of 0.1415 in 2010-2014. Dewi & Yasa (2017) stated that the average environmental disclosure is 0.2053 in 2012-2015 in non-financial companies in Indonesia. Meanwhile Ningsih (2017) found the average environmental disclosure of 0.34.…”
Section: Introductionmentioning
confidence: 99%